2022
DOI: 10.3892/br.2022.1504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SARS‑CoV‑2 mRNA vaccines on platelet polyphosphate levels and inflammation: A pilot study

Abstract: Platelets function as immune cells in conjunction with white blood cells, targeting invading pathogens and inducing immune reactions. Intercellular communications among these immune cells are partly mediated by platelet polyphosphate (polyP), which was originally recognized as a thrombotic and hemostatic biomolecule. To determine the involvement of polyP in SARS-CoV-2-mRNA vaccine-induced immune responses, specifically in inflammatory responses, the effects of mRNA vaccines on platelet polyP levels were examin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…An automated hematology analyzer was used to determine blood cell count and hemoglobin (HGB) levels. Samples within the optimized range were probed with 4 μl/sample (4 μg/ml) DAPI for 30 min at room temperature (18–22°C) and directly subjected to fluorescence measurements using a fluorometer (FC‐1; Tokai Optical Co., Ltd.) with excitation and emission wavelengths of 425 and 525 nm, respectively (Uematsu et al, 2022 ; Watanabe et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An automated hematology analyzer was used to determine blood cell count and hemoglobin (HGB) levels. Samples within the optimized range were probed with 4 μl/sample (4 μg/ml) DAPI for 30 min at room temperature (18–22°C) and directly subjected to fluorescence measurements using a fluorometer (FC‐1; Tokai Optical Co., Ltd.) with excitation and emission wavelengths of 425 and 525 nm, respectively (Uematsu et al, 2022 ; Watanabe et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The number of non‐fixed, living platelets suspended in PBS was adjusted to a density ranging between 2.5 and 5.0 × 10 7 /100 μl, mixed with 10 μl WST‐8 solution (Dojindo Molecular Technologies, Inc.), and incubated for 1 h at room temerature (18‐23°C) under a dark environment. After centrifugation, the supernatants were analyzed using a spectrophotometer at 450 nm (SmartSpec Plus; Bio‐Rad Laboratories, Inc.), as described previously (Uematsu et al, 2022 ; Watanabe et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood cell counts were performed using an automated hematology analyzer (pocHi V-diff, Sysmex Corporation, Kobe, Japan) before centrifugation and measuring platelet polyP levels to prepare the platelet suspension and adjust platelet counts, respectively [ 8 , 9 ]. If the histograms of platelet distribution did not display a smooth curve, the samples were discarded and not subjected to further polyP quantification.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies [ 7 , 8 ], the DAPI-dependent assay technique was improved, and its usefulness and reliability were validated. In a subsequent study, we found [ 9 ] that platelet polyP might suppress the SARS-CoV-2-mRNA vaccine-induced adverse effects following the first vaccination in young female participants, but not following the second vaccination. More recently, we found that platelets in professional athletes who exhibit higher metabolic activity than non-athletes may display a distinct regulatory system for maintaining the ATP–polyP balance, because polyP levels are correlated with cytoplasmic NADH levels [ 10 ].…”
Section: Introductionmentioning
confidence: 96%